Design and development of a manpower allocation system - Zhang, Fan (2012)
In this paper, I will introduce an user-interfaced software for manpower allocation based on a linear programming model with consideration of expectation. Firstly, a brief introduction of manpower allocation background and some basic concepts will be given. Followed by that, a review of linear programming models, personality and technical specialization in human resource management will be discussed in literature review part. Then I will explain a new linear programming model, MOPM model, as well as the idea of expectation in manpower allocation aspect. After this, the implementation of MOPM model in Java code is shown. Then, I will explain the workflow and thinking of the software by using Unified Modeling Language (UML) and graphical interfaces. And a case study by using this software will be introduced in next chapter. Finally, I will conclude what I did in this project and propose some ideas which may focus on in future.